Policy Implementation Community Empowerment Through Strengthening The Role Of Coordination Pokja Posyandu To Prevent Stunting In Bangun Harja Village, Seruyan Hilir East District, 2023 - Astrid Novita; Rakhman, Zauhari (Sean Institute, 2024)
The role of the village level posyandu working group is very strategic, one of which is coordinating the implementation of programs related to the development of posyandu in an effort to prevent stunting in the posyandu working area. The aim of the research is to evaluate the role of posyandu working group coordination in preventing stunting in Bangun Harja Village, Seruyan Hilir Timur District in 2023. This research is a qualitative research. The informants for the interview were 1 coordinator and 1 member of the posyandu working group in Bangun Harja village, while the supporting informants included: 1 head, 1 nutrition officer, 1 health promotion officer at Kualua Pembuang II Health Center, and 2 mothers with toddlers. in Bangun Harja village taken using the purposive sampling method. Data analysis in qualitative research. The research results of the Bangun Harja Village Posyandu Working Group have been organizationally established and are not functioning optimally due to the lack of human resources and facilities/infrastructure and there is no funding for the Bangun Harja Village Posyandu Working Group and coordination is only carried out by the Provincial and Regency Level Posyandu Working Groups directly with the community. to Posyandu cadres and the community, so that coordination of the Posyandu Working Group in Bangun Harja Village did not work due to the lack of clear technical instructions regarding the role of the Posyandu Working Group in preventing stunting. Then we look at the 5 M's, namely: 1) There is no clear planning, organization and direction, 2) Human resources in the Posyandu Working Group have not been empowered maximally, 3) There is no infrastructure such as weight measuring scales, Upper Arm Circumference measuring devices. and Toddler Head Circumference Measuring Tools, 4) There is no technical guidance regarding duties and functions, and 5) There is no budget yet, both operational and transportation budgets for activities in carrying out their duties to prevent stunting in Bangun Harja Village.